The "Let's Get Alarmed!" initiative: a smoke alarm giveaway programme. Issue 3 (1st September 1999) - DiGuiseppi, Carolyn; Slater, Suzanne; Roberts, Ian; Adams, Lucy; Sculpher, Mark; Wade, Angela; McCarthy, Mark
Abstract : Objectives —To reduce fires and fire related injuries by increasing the prevalence of functioning smoke alarms in high risk households. Setting —The programme was delivered in an inner London area with above average material deprivation and below average smoke alarm ownership. The target population included low income and rental households and households with elderly persons or young children. Methods —Forty wards, averaging 4000 households each, were randomised to intervention or control status. Free smoke alarms and fire safety information were distributed in intervention wards by community groups and workers as part of routine activities and by paid workers who visited target neighbourhoods. Recipients provided data on household age distribution and housing tenure. Programme costs were documented from a societal perspective. Data are being collected on smoke alarm ownership and function, and on fires and related injuries and their costs. Results —Community and paid workers distributed 20 050 smoke alarms, potentially sufficient to increase smoke alarm ownership by 50% in intervention wards. Compared with the total study population, recipients included greater proportions of low income and rental households and households including children under 5 years or adults aged 65 and older. Total programme costs were £145 087. Conclusions —It is possible to implement a large scale smoke alarm giveaway programme targeted to high risk households in a densely populated, multicultural, materially deprived community. The programme's effects on the prevalence of installed and functioning alarms and the incidence of fires and fire related injuries, and its cost effectiveness, are being evaluated as a randomised controlled trial.